Requesting Strategies in The Doorman Movie Using the Trosbrog's Theory (1995) - Alwiya Saboe; Hamzah A. Machmoed; Noer Jihad Saleh (Hasanuddin University, 2022)
In conducting this research, the researcher uses the descriptive qualitative method. This research is qualitative because the data are in the form of words and are analyzed based on the natural setting or context. this research to show the division of request strategy in speech act in the doorman movie. The doorman movie is an action genre movie which mostly from the data obtained is imperative. , the results reveal eight of Trosbrog's (1995) seven types of speech act techniques used by the characters in dialog in the movie entitled